Promotion Strategy for OHS Management of Chemical Hazard Factors in Hospitals: Literature Review - Anetya Martiadevi Lestari (Fakultas Kesehatan Masyarakat, Universitas Muhammadiyah Palu, 2024)
Introduction: OHS or Occupational Safety and Health in hospitals is one of the activities carried out to maintain and protect human resources so that they can protect themselves and patients. Apart from that, human resources in the hospital sector are not only aimed at doctors, but also at patient companions, patients, employees, staff and all components involved in the hospital. Objective: Analyze OHS promotion management strategies regarding chemical hazard factors in hospitals. Method: The method used in the research uses a qualitative type. The approach used is a descriptive literature review. Result: There are various types of chemical hazards found in hospitals, for example found in laundry services where the ingredients contain quite high risks and dangers. For example, clax allegro has been proven to have corrosive and carcinogenic properties. Harmfull has the property of causing eye damage and burns. Anios has flammable vapor properties, sensitizer, and so on. Conclusion: One of the factors that needs to be considered in the management strategy is related to the management of medical waste which is related to chemical factors. The remaining chemicals used in hospitals or what is called waste must first go through several processes, for example sorting, storing, transporting and managing according to the characteristics of the chemicals found in the hospital. The management carried out has the aim of minimizing the dangers posed by the chemicals used in the hospital